INNOVATIVE METHODS IN PEDAGOGY, TRANSLATION AND FOREIGN LANGUAGE TEACHING IN MODERN EDUCATION - Salimova Silvana Rustemovna (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
In the modern era of education, innovation has become a key factor in improving the quality of teaching and learning. Pedagogy, translation, and foreign language education are areas that require continuous renewal, creativity, and the use of modern technologies. This article explores how innovative approaches — including digital tools, project-based learning, and communicative practices — can make language and translation classes more effective and motivating. Practical examples from student and teacher experience are also discussed.